STUDY EKSPERIMENTAL PERILAKU ALIRAN FLUIDA PADA SAMBUNGAN BELOKAN PIPA - Hariyono, Hariyono; Rubiono, Gatut; Mujianto, Haris (Virtual of Mechanical Engineering Article, 2016)
Pipe  network  is  common  instalation  in  daily  life.  Elbow  is  a  component  in  pipe  network.This research is aimed to get fluida flow behavior in elbow. The experiment is conduct with fluid flow apparatus with number of elbows. The apparatus consist ¾ inch diameter of PVC pipe and a pump which generate water flow and pressure. Volume flow rate is vary by valve opening which are ¼, ½, ¾ and full open. The flow rate is measured using flow meter and a stopwatch.This flow rate is used to get Reynold number. The pressure before and after elbow are measured using U tipe manometer. The measurement takes 5 times at 5 measurement points. The result shows that fluid  flow  tend  to  have  pressure  decreasing.  Much  elbow  number  caused  greater  pressure decreasing.  The  maximum  pressure  occur  at  Re  3049,60  at  first  point  measurement  which  is592,52 kg/m2. The minimum pressure occur at Re 1532,45 at fifth point measurement which is 8,18 kg/m2.